The effects of Prandtl number on natural convection in triangular enclosures with localized heating from below - Koca, Ahmet; Öztop, Hakan Fehmi; Varol, Yasin (Pergamon-Elsevier Science Ltd, 2007)
The effect of Prandtl number on natural convection heat transfer and fluid flow in triangular enclosures with localized heating has been analyzed by solving governing equations of natural convection in streamfunction-vorticity form with finite-difference technique. Solution of linear algebraic equations was made by Successive Under Relaxation (SUR) method. Bottom wall of triangle is heated partially while inclined wall is maintained at a lower uniform temperature than heated wall while remaining walls are insulated. Computations were carried out for dimensionless heater locations (0.15 <= s <= 0.95), dimensionless heater length (0.1 <= w <= 0.9), Prandtl number (0.01 <= Pr <= 15) and Rayleigh number (10(3)<= Ra <= 10(6)). Aspect ratio of triangle was chosen as unity. It is observed that both flow and temperature fields are affected with the changing of Prandtl number, location of heater and length of heater as well as Rayleigh number. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Prandtl number; natural convection; partial heating; triangular enclosure